2020
DOI: 10.1080/15376516.2020.1771803
|View full text |Cite
|
Sign up to set email alerts
|

Manganese-induced neurotoxicity and the potential protective effects of lipoic acid andSpirulina platensis

Abstract: At the end of the experiment, the neurobehavioral tests (sucrose preference, Morris water maze, inverted screen test) were done.The final body weight of each rat was recorded for evaluating the body weight changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…An effect that was demonstrated to be mediated by the induction of caspase 3 gene expression in a similar rat model of lead-induced neurotoxicity, using spirulina maxima [ 56 ]. Spirulina platensis also demonstrated a neuroprotective activity in other neurotoxic paradigms, in particular in sodium fluoride and manganese treated animals, always associating the protective activity to an antioxidant effect [ 57 , 58 ]. The neuroprotective antioxidant activity of spirulina has also been demonstrated more directly in models of cerebral ischemia-reperfusion injury in rats.…”
Section: Spirulina and Brain Health: In Vivo Evidence And Related Mechanism Of Actionmentioning
confidence: 99%
“…An effect that was demonstrated to be mediated by the induction of caspase 3 gene expression in a similar rat model of lead-induced neurotoxicity, using spirulina maxima [ 56 ]. Spirulina platensis also demonstrated a neuroprotective activity in other neurotoxic paradigms, in particular in sodium fluoride and manganese treated animals, always associating the protective activity to an antioxidant effect [ 57 , 58 ]. The neuroprotective antioxidant activity of spirulina has also been demonstrated more directly in models of cerebral ischemia-reperfusion injury in rats.…”
Section: Spirulina and Brain Health: In Vivo Evidence And Related Mechanism Of Actionmentioning
confidence: 99%
“…Spirulina platensis (SP) is a type of cyanobacteria that thrives in warm, alkaline freshwater lakes [9]. Several studies have shown that SP has potential benefits for brain health [9][10][11]. It has antioxidant, anti-inflammatory, and neuroprotective properties [9,10,12].…”
Section: Introductionmentioning
confidence: 99%
“…It has antioxidant, anti-inflammatory, and neuroprotective properties [9,10,12]. It mitigates mental fatigue via preventing endothelial damage to cerebral blood vessels [10,11]. Additionally, it improves motor, language, and cognitive skills [13].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, SP supplementation increased spatial learning but had no effect on memory retention. There are limited studies showing the positive effects of SP on learning and memory in stress, schizophrenia, and neurotoxicity models in rats (Haider et al, 2021; Ibrahim et al, 2020; Moradi‐Kor et al, 2019). There are no studies on the effect of SP on learning and memory in HFD.…”
Section: Discussionmentioning
confidence: 99%